Hidden order : a thriller - Thor, Brad (New York : Pocket Books, 2014)
When a string of high-profile kidnappings in Washington, D.C., escalate upon the discovery that the victims are being murdered, an eventual ransom demand triggers terror throughout the country and covert counterterrorism operative Scot Harvath is summoned to put an end to the crisis.
Keywords: Harvath, Scot (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; Kidnapping -- Fiction; Washington (D.C.) -- Fiction